2015
DOI: 10.1371/journal.pone.0129428
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Metastasis of Unknown Primary Origin at the Initial Visit: A Retrospective Analysis of 286 Cases

Abstract: BackgroundSkeletal metastasis is a common metastatic event for several carcinomas, and the treatment for skeletal metastasis of unknown primary (SMUP) are a critical issue in cancer therapy. Making a diagnosis of the primary site is the most crucial step in the treatment of SMUP; however, the procedures are sometimes difficult and time-consuming, and the primary site often remains unknown. Therefore, to establish optimal diagnostic strategies and elucidate the overall survival rates of SMUP, we conducted this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
47
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(57 citation statements)
references
References 22 publications
3
47
0
7
Order By: Relevance
“…Bone is a common target of distant metastases in prostate cancer (Huang et al, 2015;Mai et al, 2015). The incidence of bone metastases in the process of prostate cancer development is about 65-70%, while it is found in 85-100% in patients who have died from prostate cancer (Jadaan et al, 2015;Takagi et al, 2015). Due to lack of symptoms in the onset of prostate cancer or early bone metastasis, most patients see their physician only once bone metastases have formed and produce symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Bone is a common target of distant metastases in prostate cancer (Huang et al, 2015;Mai et al, 2015). The incidence of bone metastases in the process of prostate cancer development is about 65-70%, while it is found in 85-100% in patients who have died from prostate cancer (Jadaan et al, 2015;Takagi et al, 2015). Due to lack of symptoms in the onset of prostate cancer or early bone metastasis, most patients see their physician only once bone metastases have formed and produce symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…2009, Takagi et al. 2015), we found that specific tumor markers, chest and abdominal CT, and bone biopsy were useful in order to find the primary tumor. All our patients with myeloma had a positive M protein result in serum or urine electrophoresis, and the PSA levels were elevated in all of our patients with prostate cancer.…”
Section: Discussionmentioning
confidence: 99%
“…9 A recent protocol with a change from technetium bone scan to a PET scan, and an increased panel of tumor marker laboratories, improved the rate of primary tumor identification to 88.8%. 11 When there is a known history of recent metastatic cancer, immediate needle biopsy may be used to confirm the origin of metastatic disease. This has a high likelihood of diagnosing the lesion with a reported success rate of 98.4%.…”
Section: Biopsymentioning
confidence: 99%